2014
DOI: 10.1002/chem.201404792
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth‐Metal Methyl, Amide, and Imide Complexes Supported by a Superbulky Scorpionate Ligand

Abstract: The reaction of monomeric [(Tp(tBu,Me) )LuMe2 ] (Tp(tBu,Me) =tris(3-Me-5-tBu-pyrazolyl)borate) with primary aliphatic amines H2 NR (R=tBu, Ad=adamantyl) led to lutetium methyl primary amide complexes [(Tp(tBu,Me) )LuMe(NHR)], the solid-state structures of which were determined by XRD analyses. The mixed methyl/tetramethylaluminate compounds [(Tp(tBu,Me) )LnMe({μ2 -Me}AlMe3 )] (Ln=Y, Ho) reacted selectively and in high yield with H2 NR, according to methane elimination, to afford heterobimetallic complexes: [(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 77 publications
(84 reference statements)
6
65
0
1
Order By: Relevance
“…Although the structural parameters of the Ln/M heterobimetalic complexes Ln[M(CH3)4]3 (M = Al, Ga) [21][22][23] and the derived half-sandwich [24], metallocene [25], and scorpionate complexes [10,26,27] are similar, the reactivity, in some cases, is dramatically different [10,26,27]. For example, previous studies from our laboratory revealed that [(Tp )Ln(CH3){Al(CH3)4}], which yields complexes of type III [9,10].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the structural parameters of the Ln/M heterobimetalic complexes Ln[M(CH3)4]3 (M = Al, Ga) [21][22][23] and the derived half-sandwich [24], metallocene [25], and scorpionate complexes [10,26,27] are similar, the reactivity, in some cases, is dramatically different [10,26,27]. For example, previous studies from our laboratory revealed that [(Tp )Ln(CH3){Al(CH3)4}], which yields complexes of type III [9,10].…”
Section: Introductionmentioning
confidence: 94%
“…Another synthesis strategy was developed by Evans et al, [4]. We and others succeeded in the isolation of a series of rare-earth metal complexes ( Figure 1, II-III, secondary interactions are not shown), by adopting the strategy of organoaluminum-assisted imide formation [5][6][7][8][9][10]. Similarly, deprotonation of lanthanide anilide complexes was achieved via treatment with butyllithium, affording complexes of type IV [11].…”
Section: Introductionmentioning
confidence: 99%
“…1 H, 13 C{ 1 H}, and 11 B NMR spectra were collected on Bruker AVII 700 or 600 spectrometers, a Bruker DRX-400 spectrometer, or a MR-400 spectrometer. 15 73 mmol) was placed in a 100 mL Schlenk flask and dissolved in THF (30 mL).…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…12 In the presence of alkylaluminum compounds, heterobimetallic compounds of the type [Ln]{(μ-R)(μ-NR′)AlR 2 } are obtained. 13 Bridging imido groups are also common in scandium chemistry. For example, insertion of benzonitrile into a Sc−C bond gives the μ 2 -imido complex [{C 5 H 4 (CH 2 ) 2 NMe 2 }Sc{μ 2 -NC(Ph)C 6 H 10 }] 2 , which is proposed to form through a mononuclear scandium imido intermediate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation